Humanized childbirth: the values of health professionals in daily obstetric care - Diego Pereira Rodrigues; Valdecyr Herdy Alves; Cristiane Cardoso de Paula; Bianca Dargam Gomes Vieira; Audrey Vidal Pereira; Laena Costa dos Reis; Giovanna Rosário Soanno Marchiori; Maria Bertilla Lutterbach Riker Branco
ABSTRACT Objective: To understand health professionals' values in the process of thinking and feeling about obstetric care, based on their experienced needs in the care process. Methods: Phenomenological study based on the Schelerian framework, with 48 health professionals from four maternity hospitals within the Metropolitan Region II of the state of Rio de Janeiro. Data collection was done through a phenomenological interview; and the analysis, with the Ricoeurian methodological framework. Results: The vital value was signified in care centered on physiological processes, for an individualized and safe monitoring. The ethical value was signified in the attitudes that provide women with autonomy in their way of giving birth, and recognize dialogue as a process of sympathy, affection, and bonding. Conclusion: The resignification of obstetric practice, articulated with public policies in the field of delivery and birth, supported by a vital ethical value, positively contributes to the humanization of care for women.